Bioativos extraídos da nêspera (Eriobotrya japonica Lindl) aplicados à conservação de laranja e suco de laranja - Amanda Neris dos Santos (2018)
The loquat (Eriobotrya japonica Lindl.) is a fruit which has in its chemical constitution acids that act as antimicrobials. Among them, ursolic acid is studied while present in the fruit and as isolated triterpenic acid. There is a relation between the consumption of loquat and human health, and adding these compounds to the formulation of food products reveals improvements to industrialized products. Due to its low toxicity, ursolic acid can be introduced into a constant consumption food matrix, not only because it has the characteristic of an organic preservative, but also because of its health benefits such as hepatoprotective and cardiovascular protection, antihyperlipidemic, antitumor and antidiabetic, anti inflammatory and antiaging effects. The objective of this study was to verify the antimicrobial potential of the loquat extract and to evaluate quality and sensorial parameters of oranges and orange juices with the application of the extract. Colorimetric analysis, mass loss, mechanical properties and classical descriptive sensory analysis were performed in the oranges; in the extract the bioactive compounds and the minimal inhibitory concentration were determined; the orange juices were analyzed for bioactive compounds, quality and sensory parameters by Pivot Profile and Projective Mapping. The pulp, pulp and seed and seed extract from the loquat remained diluted in water and stored at -20 ° C. The minimum inhibitory concentration analysis identified an antimicrobial action in 1.66% extract concentration against Staphylococcus aureus ATCC 29213 and 3.33% against Escherichia coli ATCC 35218. The selected loquat extract was added in the orange coating and in the processing of orange juice at concentrations of 0, 2.5 and 5% extract. In the oranges, the analysis of color, weight loss and mechanical properties showed no difference between the lots that were evaluated. Bioactive compounds in the extract and juices were determined by Folin-Ciocalteu and UPLC; in the juice, analyzes of soluble solids and titratable acidity showed that the ratio of samples with addition of extract did not present ideal palatable characteristics, it was observed that the proportion of free water in the reaction environment of orange juice with the highest concentration of extract remained stable. In microbiological analysis in orange juice, there were no total and thermotolerant coliforms of Salmonella spp. and molds and yeasts. The sensory analysis of orange juice by Pivot Profile showed a greater impact on the descriptors bitter, essence and acid, and the technique of Projective Mapping confirmed that the extract is perceptible at concentrations of 2.5% and 5%, however, the concentration of 1% showed vector direction to pure juice samples. This study is a pioneer and the application of 2.5% of seed extract in orange juice showed that the antimicrobial potential in a food matrix, besides the possibility of application of the hydroethanolic extract of the loquat seed in a food matrix by similarity between the sample with 1% of extract and the samples of integral orange juice.